Immune checkpoint inhibitors break whose heart? Perspectives from cardio-immuno-oncology - Yingying He; Hui Yu; Shuang Dai; Miao He; Ling Ma; Zihan Xu; Feng Luo; Li Wang (Genes and Diseases, 2024)
Immune checkpoint inhibitors (ICIs) are monoclonal antibody antagonists, which can block cytotoxic T lymphocyte antigen-4 (CTLA-4), programmed death-1/ligand-1 (PD-1/PD-L1) pathways, and other molecules exploited by tumor cells to evade T cell-mediated immune response. ICIs have transformed the treatment landscape for various cancers due to their amazing efficacy. Many anti-tumor therapies, including targeted therapy, radiotherapy, and chemotherapy, combine ICIs to make the treatment more effective. However, the off-target immune activation caused by ICIs may lead to a broad spectrum of immune-related adverse events (irAEs) affecting multiple organ systems. Among irAEs, cardiotoxicity induced by ICIs, uncommon but fatal, has greatly offset survival benefits from ICIs, which is heartbreaking for both patients and clinicians. Consequently, such cardiotoxicity requires special vigilance, and it has become a common challenge both for patients and clinicians. This article reviewed the clinical manifestations and influence of cardiotoxicity from the view of patients and clinicians, elaborated on the underlying mechanisms in conjunction with animal studies, and then attempted to propose management strategies from a cardio-immuno-oncology multidisciplinary perspective.